FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE ELECTRONICS SPECIALISTS IN INSTITUTIONS OF PROFESSIONAL HIGHER EDUCATION - Kokarіeva, Angelika; Shutkov, Kostiantyn (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The important task for institutions of professional pre-higher education is the current employment of students in the educational process, factors that influence their learning motivation, the effectiveness of knowledge acquisition, further professional orientation, and the use of acquired knowledge in future professional activities. The study examined the key components of student engagement in institutions of professional pre-higher education as an important prerequisite for the formation of sustainable learning motivation, and also analyzed the role of teachers' pedagogical skills in maintaining interest in learning. It is substantiated that student engagement in learning increases under the conditions of improving the educational program, updating core disciplines, and improving the quality of teaching. A key factor in the formation of professional competence is the teacher's pedagogical skills, which include the ability to adapt teaching methods according to the individual characteristics of students, contribute to the development of independence, creativity, and internal motivation for learning. The importance of the multi-paradigm approach as a methodological basis that ensures efficiency in solving the problem of student engagement is actualized. It combines key provisions of the systemic, personal-activity and motivational approaches, which together create the necessary conditions for the development of sustainable learning motivation and successful professional training of future electronics specialists. The main goal of this study is to identify and analyze the problems that arise in the process of forming the professional competence of future electronics specialists in institutions of professional pre-higher education in the context of the rapid transformation of the labor market; as well as in developing proposals for professional training to increase the efficiency of the educational process and the interest of applicants in learning; analyzing effective methods of pedagogical facilitation and modern approaches that allow teachers to recognize and develop applicants' interests in certain areas in the professional field, as well as to contribute to the formation of their educational motivation and cognitive involvement. There were used several general scientific methods in the process of research: analysis, synthesis, classification, comparison, etc. as a result, it was found that rapid changes in the labor market and in the technological sphere require constant updating of professional training of future electronics specialists in institutions of professional pre-higher education. The development and integration of modern curricula that meet current trends in the industry is an important step towards increasing the efficiency of the educational process. For the successful adaptation of students to the requirements of the labor market, it is necessary to use innovative methods of pedagogical facilitation that will contribute to the development of learning motivation and cognitive involvement of students. As a conclusion, we assume that rapid changes in economic and technological spheres in institutions of professional pre-higher education for future electronics specialists require regular updating of curricula. This involves the integration of modern knowledge and technologies, which will allow future specialists to navigate current trends in the development of their industry and effectively apply the acquired knowledge in further professional activities. Key words: institutions of vocational pre-higher education; acquirers; educational professional program; educational motivation; pedagogical skill; pedagogical facilitation; professional competence; professional training; electronics specialists.